The Impact of Mobile Applications on Quran Education: A Survey of Student Performance and Satisfaction - Hakimi, Musawer; Mursal AKRAMI; Maliha AHRARI; Khatera AKRAMI; Fazila AKRAMI (RADINKA JAYA UTAMA PUBLISHER, 2024)
Mobile applications have emerged as innovative tools in Quranic education, presenting opportunities to enhance learning experiences and engage students effectively. This study aims to assess the impact of mobile applications on Quranic education through a comprehensive survey-based investigation. The research method involved designing a structured questionnaire to gather data on various dimensions, including application usage patterns, effectiveness ratings, contributions to educational improvement, perceived impacts on students' understanding and retention of Quranic knowledge, enhancement of student performance, and comparisons between traditional and mobile application-based learning methods. The population for this study consisted of students enrolled in online university programs with a focus on Quranic education, with a sample size of 60 respondents contributing valuable insights. Quantitative data analysis encompassed descriptive statistics and inferential methods, enabling a thorough examination of survey responses and relationships between variables. The findings reveal diverse usage patterns of Quranic education applications, with respondents attributing significant value to mobile applications in enhancing Quranic education. Positive perceptions regarding the effectiveness of mobile applications in improving student performance and understanding of Quranic knowledge were prevalent among participants. Additionally, a clear preference for mobile application-based learning emerged over traditional methods. The study underscores the importance of leveraging mobile technology to enrich Quranic education and highlights avenues for future research in this domain. Overall, the research contributes to advancing knowledge on the role of mobile applications in Quranic education and informs pedagogical practices in digital learning environments.